Analisis Perbedaan Konsep Pinjaman Dari Imam As Syafi’i, Imam Hambali & Imam Al Ghazali - Ahmad Firdaus Lingga; Hendra Hendra (Universitas Dian Nuswantoro, 2022)
This study aims to analyze the differences in the concept of borrowing from Imam Shafi'i, Imam Hambali and Imam al-Ghazali. This research is a descriptive research with a qualitative approach. The data collection method is in the form of literature study. The results of the study show that in Islam there is a concept of loan where in the Islamic world the concept of loan is also known as Qardh which is basically a loan from someone to another party with the aim of helping him. Based on the opinions of 4 mazhab, including the Shafi'i and Hambali mazhab, the concept of borrowing, also known as qardh, is permissible for a Muslim to do and forbids a Muslim from taking advantage of practices that are considered usury. Meanwhile, from Imam Al Ghazali's point of view, the concept of loan can be seen from the idea of qardh al-hasan, namely a loan transaction which in practice is the fulfillment of a moral obligation, especially as a Muslim, and no financial reward is claimed for it.